2009
DOI: 10.1523/jneurosci.4736-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Brain-Derived Neurotrophic Factor Depends on Amyloid Aggregation State in Transgenic Mouse Models of Alzheimer's Disease

Abstract: Downregulation of brain-derived neurotrophic factor (BDNF) in the cortex occurs early in the progression of Alzheimer’s disease (AD). Since BDNF plays a critical role in neuronal survival, synaptic plasticity, and memory, BDNF reduction may contribute to synaptic and cellular loss and memory deficits characteristic of AD. In vitro evidence suggests that amyloid-β (Aβ) contributes to BDNF downregulation in AD, but the specific Aβ aggregation state responsible for this downregulation in vivo is unknown. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
134
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(148 citation statements)
references
References 75 publications
11
134
2
1
Order By: Relevance
“…S6). These results are consistent with previous reports of reduced BDNF levels in AD brains and other animal models (27)(28)(29). We next assessed how BDNF protein levels change in response to CBP gene transfer.…”
supporting
confidence: 90%
“…S6). These results are consistent with previous reports of reduced BDNF levels in AD brains and other animal models (27)(28)(29). We next assessed how BDNF protein levels change in response to CBP gene transfer.…”
supporting
confidence: 90%
“…Evidence has suggested that dysfunction of BDNF is a possible contributor to the pathology and symptoms of AD (Tapia-Arancibia et al 2008). BDNF is found to be decreased in APP/PS1 mice even in the early stages of AD-like pathology (Peng et al 2009;Hsiao et al 2014). Apart from BDNF, other neurotrophic factors, such as nerve growth factor (NGF) and glial cell-derived neurotrophic factor (GDNF), are also involved in normal aging and AD (Allen et al 2013;Budni et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence indicates that BDNF levels are decreased in brains of AD patients (Hu and Russek, 2008;Peng et al, 2005;Zuccato and Cattaneo, 2009) and APP transgenic mice (Francis et al, 2010;Peng et al, 2009). We first characterized changes in BDNF levels in the 5XFAD transgenic mouse model at different ages ranging from 3 to 18 months (Figure 1).…”
Section: Bdnf Declines Early During the Disease Progression In 5xfad mentioning
confidence: 99%